Purchasing Power Parity Hold in Major SAARC Countries? Panel Cointegration Analysis - Mehmood, Rashid; Younas, Muhammad Zeeshan (Quarterly Journal of Econometrics Research, 2019)
In an effort to provide a better understanding of the large variation in price levels between countries, this paper examines the validity of the purchasing power parity (PPP) hypothesis using monthly data of SAARC countries over the period of 2000-2017. We utilized four econometric tests to examine the existence of this hypothesis in the understudy region. Panel results show that PPP seems to be moderately held in a panel of SAARC, while in the country by country analysis we find partial support of PPP for all economies. We also find that the price and exchange rate have a long-run relationship while ECM analysis shows that the exchange rate and price differential are correlated in the short run, and price and exchange rate have bidirectional causality relationship. In addition, the dummy variable analysis shows that the Global Financial Crisis 2007-08 significantly affect the SAARC countries exchange rate in terms of depreciation. However, these types of external shocks do not have any permanent effect on the real exchange rate and other things remaining the same, no active policy intervention is warranted for the sustainability of external balance.